Dictionary of forestry and wildlife sciences - Bebarta, Kailash Chandra (New Delhi Concept Publishing, 2011)
The dictionary of wildlife science in intended to provide and updated resource for the present day readers in understanding words in its current perspective from forestry, wildlife science and may other allied subjects such as ecology, environmental economics, geomatics, etc.
Keywords: Forests and forestry - Dictionaries; Wildlife management; IFoS as an author; Indian Forest Service